Translation and cross cultural adaptation of the Pediatric Motor Activity Log-Revised scale - Gabriela da Silva Matuti; Juliana Firmo dos Santos; Ana Carolina Rodrigues da Silva; Rafael Eras-Garcia; Gitendra Uswatte; Edward Taub (Arquivos de Neuro-Psiquiatria)
ABSTRACT The standardized instrument developed to assess the use of the affected upper limb in children with cerebral palsy (CP) is the Pediatric Motor Activity Log Revised (PMAL-R). Objectives To translate PMAL-R and adapt for the Brazilian culture; analyze the reliability and the internal consistency of the Brazilian version. Method Translation of PMAL-R to the Portuguese-Brazil and back translation. The back-translated version was revised by the authors of the scale. The final version was administered to a sample of 24 patients with spastic hemiparesis CP between 2–8 years. Results The reliability intra and inter-rater were suitable (how often = 0.97 and 0.98, how well = 0.98 and 0.99 respectively) and so the internal consistency (0.98). Conclusion The Brazilian version of PMAL-R has adequate internal consistency, reliability intra and inter raters and can be used to assess the spontaneous use of the upper limb of children with CP type spastic hemiparesis, aged 2–8 years.